An Analysis of Road Traffic Collisions on Roads of Sabarkantha District of Gujarat - Mitesh K Patel; GP Kartha (Medsci Publications, 2010)
This study on road traffic accidents in Sabarkantha district conducted from January to December 2002 among National and State Highways and town/ village roads examines the pertinent epidemiological variables thereof. Of the 512 event of road traffic accidents 81.6% were non-fatal and 18.4% were fatal with domination of pedestrian accidents (37.8%). The highest events (40%) took place on National highway followed by State highways (31.4%) and town/village roads (28.5%) and events like "vehicle head on", "vehicle hit from back", "vehicle hit from side" and "run off the road" were higher on National highway. The study points to the need for proper traffic management at all levels starting from the village and town roads to the State and National highways to control the avoidable morbidity and mortality associated with road traffic accidents.